Utilization of agro-industrial byproducts as low-cost nutrient sources for production of kefiran and lactic acid by Lactobacillus kefiranofaciens - Apisara Iadcharoen; Benjamas Cheirsilp; Jariya Ruangwicha; Sirasit Srinuanpan; Sompong O-Thong (Carbon Resources Conversion, 2025)
Kefiran is an exopolysaccharide derived from kefir grains that has antioxidant and antimicrobial properties. The high production cost of kefiran is primarily attributed to the expensive fermentation media. Therefore, the use of byproducts from agro-industries could present an economically favorable alternative. In this study, locally available mature coconut water (MCW) and whey lactose (WL) were used as cost-effective nutrient sources for kefiran production by Lactobacillus kefiranofaciens JCM 6985. MCW gave a higher yield of kefiran and acid than WL and was comparable to the commercial medium. The optimal sugar concentration for kefiran and acid production from MCW was 30 g/L, and the pH control during cultivation could alleviate the inhibitory effect of acidic pH and enhance kefiran and acid production. When the MCW was added with yeast extract at 3 g-nitrogen/L, the kefiran and acid production increased up to 3.26 ± 0.03 g/L and 15.5 ± 0.7 g/L, respectively. Moreover, the kefiran and acid production was scaled up in the bioreactor and enhanced by the repeated-batch cultivation for six cycles. The structure analysis indicated that kefiran produced by L. kefiranofaciens when using MCW had a similar structure to that extracted from kefir grains. The findings demonstrate promising methods for cost-effective production of kefiran and lactic acid using inexpensive nutrient sources such as MCW.